The Role of School Principal Supervision in Improving the Performance of Certified Teachers - Nazariah Nazariah; Suparta Rasyid; Riandi Marisa (STAI Miftahul Ula Nganjuk, 2025)
This study explores the role of school principals in the supervision process to enhance certified teacher performance at MIN 1 and MIN 5 Pidie Jaya. Data were collected through observation, interviews, and document analysis. The findings reveal that effective supervision involves three key components: (1) Planning: Principals collaborate with teachers to establish structured schedules, clear goals, and suitable techniques for accurate performance assessments, fostering a supportive environment that boosts teacher performance. (2) Implementation: Supervision is carried out through the use of assessment instruments, class observations, and evaluation of teaching materials and learning outcomes, complemented by regular guidance and motivation. (3) Evaluation: Principals provide structured feedback and follow-up actions, such as improvement plans and additional training, to facilitate teachers’ professional development. The study concludes that the successful implementation of planning, execution, and evaluation in the supervision process at MIN 1 and MIN 5 Pidie Jaya significantly enhances teacher performance and contributes to improving the overall quality of education.